ESTUDIO DE LA COMUNICACIÓN INTERNA EN LA INDUSTRIA HOTELERA DE PUERTO VALLARTA JALISCO - Cristhell Abigail Díaz Ramos; Manuel Ernesto Becerra Bizarrón; Alma Azucena Enríquez Lugo (European Scientific Journal, ESJ, 2014)
Tourism is the set of trips for pleasure, for professional or commercial reasons, that tourism is the travel and stay engaged people in different places outside their usual environment, for a specified period. This results in spaces where tourists can stay at the time of your stay, this is where the hotels providing accommodation services arise. One of the main problems encountered in the hospitality organizations in Puerto Vallarta, is the lack of intervention actions to help achieve improvements and increases in productivity through climate studies in organizations.The University Center of the coast in order to identify the elements of internal communication and productivity in business and how these affect the productivity of the employees of all levels took place. This research is not Experimental or Ex-post facto type because such research observes the phenomena as they occur in their natural context.